Nicolae Răutu – actor al scenei şi ﬁlmului (Confluenţe Bibliologice, 2012)
One of our actors of high cultural value was the Romanian actor Colea Răutu. After graduating from primary school, he attended the first two grades of the "Ion Creangă" High School between 1923-1925. He lived to be 96 years old and was appreciated by the great Romanian actors Constantin Tănase and Radu Beligan. Colea Răutu stood out in the classical and modern repertoire. He played the role of Tartar extraordinarily alongside other theater stars.
Keywords: Nicolae Răutu (1912 – 2008); actori basarabeni; actori de teatru și film